Deadly Coal Social Campaign in Environmental Policy Advocacy for Indigenous Community of Kalimantan - Winda Dwi Astuti Zebua; Abdul Rahman; Syifa Astasia Utari; Wisnu Hasanudin; Dwinarko Dwinarko (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2023)
In the midst of the high production of coal to meet the energy needs of society, JATAM strives to carry out a social campaign for environmental advocacy in the indigenous communities of Kalimantan. The purpose of this article is to describe the management of JATAM's deadly coal campaign in advocating for the environmental rights of indigenous communities in Kalimantan due to coal mining activities. A qualitative research approach was chosen to uncover data to address these objectives. The data collection techniques employed were interviews and documentation through online media monitoring. The data analysis technique utilized three stages: data reduction, data presentation, and drawing conclusions. The results obtained indicate that the campaign aims to advocate for the rights of indigenous communities in Kalimantan to have a safe and healthy environment without mining contamination. The primary target audience includes indigenous communities and the government. In its implementation, JATAM engages in discussions and provides writing training for indigenous communities. Furthermore, JATAM collaborates with Greenpeace and other international NGOs to conduct on-the-ground lobbying of government policies through various actions. The targeted communities have shown a change in attitude and behavior, demonstrating acceptance and willingness to learn about the impacts of mining and their rights to life in their indigenous land.